Subjective Well‐Being Anak Dari Orang Tua Yang Bercerai - Pracasta Samya Dewi; Muhana Sofiati Utami (Jurnal Psikologi, 2008)
This qualitative study aims to know how the psychological dynamic of Subjective Well‐Being (SWB) of children is from divorced parents. This research involved three children from divorced parents as subject. The subjects’ ages were between 18‐21 years old. Data was collected through in‐depth interview, participative observation, and self report method. Findings indicated that there were three conditions of subjective well‐being of children from divorced parents. The first condition is the condition before the parent`s divorced, whereas the second and the third are the condition after the parent`s divorced. The first condition shows that children from divorced parents have low level of subjective well‐being before their parents divorced. It is mainly because of the parental conflict and the low level of family to spend time together which araised motional attachment. In the second condition, children from divorced parents still have low level of subjective well‐being that mainly because of the parental divorced, parental attitude that never told to their child about the divorced, and the decrease of parental attachment following the divorced. The third condition, children from divorced parents show the higher level of subjective well‐being that mainly because of the acceptance of children for the parents divorced. This acceptance leads children from divorced parents feeling positive affect and life satisfaction.